Construction Techniques and Quality Test and Evaluation of Lightweight Cellular Concrete Mixed with Fly Ash as Subgrade Material - Xin Liu; Chengwei Ni; Hong Ji; Shuyan Tan; Baoning Hong (Advances in Materials Science and Engineering)
To improve the comprehension and utilization of lightweight cellular concrete mixed with fly ash (LCCF) and ensure project quality in subgrade construction engineering, the construction techniques and quality control measures of LCCF are studied in this paper. The corresponding research contents, based on a specific project case located in Guangdong Province, are as follows. Firstly, the construction technology process and technological measures are put forward, according to the site construction conditions and quality requirements. Secondly, the feasibility of indoor mixture ratio is further verified by measuring the fluidity, wet density, and strength on-site. Thirdly, the suitable pouring thickness of the single layer and reasonable interval time between layers are determined by the vertical delamination test and surface strength test. In this paper, the indoor mixture ratio of LCCF has been improved through tests such as single factor test and multifactor orthogonal test considering factors like fly ash, water-binder ratio, and foam. Some highlights of this article are as follows: the preparation methods of lightweight concrete in laboratory and in situ are given. And two patented test devices are used for the strength test along with the depth and surface strength test, respectively. Besides, the practical engineering case is Lianjing Bridge, of which mileage pile number is K80 + 679.679∼K80 + 760.113, which is part of a highway in Zhaoqing City, Guangdong Province, China.